IMPORTANCE OF ENGLISH IN OTHER SPHERES, ESPECIALLY IN BUSINESS AND ECONOMICS (SCIENCE TIME JOURNAL, 2024)
This article highlights the significance of English language proficiency in various fields, with a specific focus on its importance in business and economics. English has emerged as the global language of communication, and its mastery is crucial for professionals seeking success in today's interconnected world. In the realm of business, English proficiency facilitates effective communication, negotiation, and collaboration with international partners, customers, and suppliers. It enables professionals to navigate global supply chains, deliver quality customer service, protect intellectual property, and engage in international marketing and branding efforts. Moreover, English proficiency plays a vital role in crisis management, economic forecasting, corporate communication, technology utilization, academic research, and social impact. The article emphasizes the multifaceted benefits of English proficiency in business and economics and underscores its role in fostering global competitiveness and cultural understanding.